Export Plan of Custom Motorcycle Deus Ex Machina from Indonesia to Japan - ALDO PRANATA; ARDION COKRODEWO; STEVE ANDERSON; PRIMA KHRISNA PRASETIO (Journal of the Community Development in Asia (JCDA), 2018)
In this paper discussed the planning of export custom motorcycle products in the company Deus Ex Machina. in this study the data used were data about the product and the export sales history of deus ex machina in Bali. In planning this export, we determined that the products to be exported were our own style custom motorbikes, because the regulations were in effect, the products to be exported had to be in the form of spare parts, with the aim of targeting market in Japan. Keyword: Custom motorcycle, Deus ex Machina, Export, L/C, spare parts.